2018
DOI: 10.1016/j.media.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Integration of temporal and spatial properties of dynamic connectivity networks for automatic diagnosis of brain disease

Abstract: Functional connectivity networks (FCNs) using resting-state functional magnetic resonance imaging (rs-fMRI) have been applied to the analysis and diagnosis of brain disease, such as Alzheimer's disease (AD) and its prodrome, i.e., mild cognitive impairment (MCI). Different from conventional studies focusing on static descriptions on functional connectivity (FC) between brain regions in rs-fMRI, recent studies have resorted to dynamic connectivity networks (DCNs) to characterize the dynamic changes of FC, since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
108
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 76 publications
7
108
1
Order By: Relevance
“…Previous studies on resting-state functional connectivity were mainly based on the temporal correlation between regional blood oxygen level-dependent (BOLD) time courses, barring an implicit assumption that functional connectivity is temporal stationary (Sporns, 2011;Jie et al, 2018). As a matter of fact, a number of researches have revealed that functional connectivity may experience a dynamic change over time (Calhoun et al, 2014), which, to a certain extent, might be attributed to the neuronal origin and related to the cognitive and vigilance state variations (Chang et al, 2013;Thompson et al, 2013;Jie et al, 2018). By measuring timevarying functional connectivity among brain regions, dynamic functional connectivity (DFC) analysis furnishes a more detailed description of interactions in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on resting-state functional connectivity were mainly based on the temporal correlation between regional blood oxygen level-dependent (BOLD) time courses, barring an implicit assumption that functional connectivity is temporal stationary (Sporns, 2011;Jie et al, 2018). As a matter of fact, a number of researches have revealed that functional connectivity may experience a dynamic change over time (Calhoun et al, 2014), which, to a certain extent, might be attributed to the neuronal origin and related to the cognitive and vigilance state variations (Chang et al, 2013;Thompson et al, 2013;Jie et al, 2018). By measuring timevarying functional connectivity among brain regions, dynamic functional connectivity (DFC) analysis furnishes a more detailed description of interactions in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the behavioural outcomes that rely on such efficient reconfigurations may be impaired, which may result in specific symptoms. Notably, accounting for temporal variability of brain activity has improved the diagnostic classification of neurodegenerative diseases, suggesting that additional information can indeed be disclosed with such approaches (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the dynamic FC were more sensitive to brain disorders than static FC. 20,21 Dynamic FC were time-resolved bivariate measures. 22 Time-varying features could be obtained from dynamic FC.…”
Section: Introductionmentioning
confidence: 99%